A procedure for validating rigid catenary models using evolutionary techniques. (February 2020) - Simarro, Montserrat; Postigo, S.; Cabrera, Juan A.; Castillo, Juan J.
Highlights: A method to validate rigid catenary mathematical models is described. Evolutionary algorithms are used to obtain the model parameters. Validations of a wide range of rigid catenary configurations are presented. The algorithm is able to deal with inaccuracies that singular supports reproduce. The algorithm has provided correctly tuned catenary models in all cases. Abstract: This paper describes a method to validate rigid catenary finite element models from modal tests. The model parameters are obtained by means of an optimization process using evolutionary techniques. The validation of rigid catenary sections is a complicated process due to the large number of parameters to be tuned. Three different scenarios have been studied to reproduce the most common assemblies of real rigid catenary sections. The performance of the algorithm has been evaluated using 45 virtual models of rigid catenary assemblies with section lengths from 48 up to 480 m and span lengths ranging from 8 to 12 m. The influence of errors in the installation of the supports has also been studied. In all cases, the algorithm has demonstrated its effectiveness in providing the correct model parameters even when a singularity in some of its supports has been introduced. According to the results, the proposed method is a valid tool to validate rigid catenary mathematical models.